Application of Wavelet LPC Excitation Model for Speech Compression - Armein Z.R. Langi (Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
This paper presents an application of linear predictive coding (LPC) excitation wavelet models for low bit- rate, high-quality speech compression. The compression scheme exploits the model properties, especially magnitude dependent sensitivity, scale dependent sensitivity, and limited frame length. We use the wavelet model in an open-loop dither based codebook scheme. With t his approach, the compression yields a signal-to-noise ratio of at least 11 dB at rates of 5 kbit/s and.